How to make a treat with Persians? An analysis of the peace negotiation process between Romans and Persians in 363 AD - Gonçalves, Ana Teresa Marques; Tavares, Wendryll José Bento (Romanitas - Revista de Estudos Grecolatinos, 2019)
The present article explores the peace talks between romans and peoples who were waging wars against the romans during the second half of the fourth century A.D. The goal is to analyze the negotiation mechanisms, sealing and maintaining treaties after conflicts involving rival peoples. For this purpose, the authors make a comparative analysis of the descriptions made by Ammianus Marcellinus in the Res Gestae about the events of 363, 367 and 374 A.D. From this, it becomes possible to know the features of diplomatic relationship that involved the Romans in that context, as well as the uniqueness of the Persians for operation of the Roman Empire.
Keywords: Romans; Persians; Foedera; Ammianus Marcellinus